A CROSS-SECTIONAL STUDY ON PATTERN AND MORTALITY OF CHEST INJURIES AMONG VICTIMS OF ROAD TRAFFIC ACCIDENT AT MORTUARY SNMMC, DHANBAD, JHARKHAND. - Kumar, Sanjeet; Kumar, Avinav; Rao, Jakka Srinivas (Student's Journal of Health Research Africa, 2024)
Background Road traffic accidents (RTAs) have a major impact on low- and middle-income countries and are one of the world's top causes of morbidity and mortality. Chest injuries from RTAs contribute substantially to trauma-related deaths and disabilities due to their severity and complexity. This study aimed to analyze the patterns and mortality of chest injuries among victims of road traffic accidents, over a six-month period. Methods A cross-sectional study including 100 RTA victims with substantial chest injuries was carried out. SPSS version 21.0 was used to gather and examine information on the kind and frequency of chest injuries, related injuries, duration of hospital stay, treatment taken, and patient outcomes. Among RTA victims receiving hospital treatment, major chest injuries were the criterion for inclusion; minor injuries and those who had passed away at the scene were not included. Results Rib fractures were the most common chest injury (45%), followed by pulmonary contusions (30%), pneumothorax (15%), hemothorax (10%), flail chest (8%), and cardiac contusions (7%). Associated injuries included extremity fractures (40%), head injuries (25%), abdominal injuries (20%), spinal injuries (15%), and facial injuries (18%). Sixty percent of patients required operative treatment, with an average hospital stay of 15 days. The mortality rate was 45%. Significant correlations were found between the type of chest injuries and age, gender, and associated injuries. Conclusion Chest injuries from RTAs are a critical public health concern, with high mortality rates and significant associated injuries. The findings highlight the need for improved trauma care and targeted preventive measures to reduce the incidence and severity of chest injuries. Recommendations Enhancing pre-hospital care, establishing more trauma centers, and improving training for trauma care personnel are essential steps to reduce mortality and improve outcomes for RTA victims with chest injuries.